Interdisciplinary speed dating augments diabetes self-management education and support to improve health outcomes. Issue 11 (November 2020) - Whitley, Heather P.; Smith, Warren D.; Hanson, Courtney; Parton, Jason M.
Highlights: Addition of Speed Dating clinic fits the Chronic Care Model. Shared decision-making via Speed Dating individualizes patient recommendations. Interdisciplinary Speed Dating clinic augments DSMES outcomes. Addition of Speed Dating clinic facilitates A1C and LDL-C goal achievement. After attending the Speed Dating clinic, patients use hospital services less often. Abstract: Objective: To determine if a novel interdisciplinary "speed-dating" clinic augments Diabetes Self-Management Education and Support (DSMES). Methods: Adult patients with diabetes attended a DSMES class. Two weeks later patients attended an interdisciplinary clinic utilizing a "speed-dating" format during which they progressed through 5 stations hosted by different healthcare disciplines at 30-minute increments: physician, pharmacist, nurse/dietitian, case manager, and psychologist. Shared decision-making was utilized to identify mutually agreeable recommendations. Change in clinical outcomes were compared for DSMES-only attenders versus Dual-attendees; utilization of emergency department and hospital services were measured 12 months before and after attending the Speed Dating clinic. This analysis represents patients attending the program during 2016. Results: Sixty-nine attended the DSMES class, 40 of whom followed-up in the "speed-dating" clinic (58% return rate). Attending the Speed Dating clinic improved A1C (p = 0.003) and LDL-C (p = 0.003) compared to the DSMES class alone. Comparatively, after attending the speed-dating clinic, patients had fewer emergency department (p = 0.366) and hospital admissions (p = 0.036), and shorter lengths of hospital stay (p = 0.030). Conclusions: The interdisciplinary "speed-dating" approach improved diabetes outcomes beyond DSMES alone and reduced utilization of hospital services. Practice implications: Patients should attend DSMES but also participate in an Interdisciplinary Speed Dating follow-up to further improve outcomes.